Analysis Of Factors Affecting Online Shopping Behavior Moderated By Technology Anxiety On Shopee’s E-Commerce Platform During The Covid-19 Pandemic (Study On Telkom University Students) - Teguh Widodo; Muhammad Akbari Salmandani (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
A survey conducted by Sirclo stated that there had been an increase of 90% since April 2020, namely since the Covid-19 pandemic, about the number of new users in several marketplaces. One of the marketplaces that has become the largest e-commerce and widely used by many people in Indonesia is Shopee. The use of e-commerce with the marketplace concept is part of the development of digital industry. Efforts made by business people to promote their product through the marketplace such as live streaming, celebrity endorsement, promotional tools, and providing online reviews facility from customers who had benefit from the products. The use of e-commerce requires digital literacy skills, both for businesses also for customers. The condition of an individual is inability to use and understand using technology can trigger anxiety in technology, so that it can have an impact on individual shopping behavior. This study aims to analyze how the effect of live streaming, celebrity endorsement, promotional tools, and online reviews moderated by technology anxiety on online shopping behavior at e-commerce Shopee during the Covid-19 pandemic that occulted at Telkom University students. The research method was quantitative research with cross-sectional study design. Data collection are carried out directly with primary data types using a questionnaire Google Form and a scale measurement, namely the Likert Scale. The population and sample in this study were students at Telkom University. The sampling technique uses non-probability sampling with purposive sampling. Data analysis was performed using (SEM) technique and the SmartPLS program for data processing